The Protection of Refugees and Displaced Persons under International Law - Khan , Syed Hammad; Anwar, Anmol; Imran, Imad; Zakir, Muhammad Hamza (Pakistan Journal of Humanities and Social Sciences, 2023)
The research paper explores the complex network of global legal measures designed to protect refugees and individuals who have been forced to leave their homes. The research carefully analyses the important rules, tools, and systems established in global law to protect the rights and welfare of people forced to leave their homes because of persecution, conflict, or humanitarian emergencies. This paper aims to shed light on the rights and responsibilities concerning refugees and displaced individuals worldwide by examining relevant treaties, conventions, and case law. The paper examines the effectiveness of current methods in addressing the difficulties encountered in maintaining these safeguards. The research helps us understand the complex problem of protecting refugees and displaced people, and it can guide future academic and policy work.